(untitled) (World Science, 2020)
The article describes the contents of the concepts of independent training and official training of the personnel of the units of the Operative and Rescue Service of Civil Protection of Ukraine, describes the practical component of their professional training directly in the units. It is established that the main types of occupations in the system of official training are lectures, seminars, practical classes, tactical-special trainings, control and testing classes. Types of practical training of rescuers are characterized: practical workout of training exercises (exercises and standards on special physical training), working out and correction of documents of operative response (plans, cards), operative-tactical study of service area and objects, solving tactical tasks, night test tactical tasks training, fire and emergency management, tactical training. At the same time, there is a contradiction between the increased level of requirements for the preparedness of rescuers in modern conditions and the traditional system of their professional training, which does not take into account changes in the extension and complication of professional tasks.